NET-(works) in arterial and venous thrombo-occlusive diseases - Zdanyte, Monika; Borst, Oliver; Münzer, Patrick (Frontiers in Cardiovascular Medicine, 2023)
Formation of Neutrophil Extracellular Traps (NETosis), accompanied by the release of extracellular decondensed chromatin and pro-inflammatory as well as pro-thrombotic factors, is a pivotal element in the development and progression of thrombo-occlusive diseases. While the process of NETosis is based on complex intracellular signalling mechanisms, it impacts a wide variety of cells including platelets, leukocytes and endothelial cells. Consequently, although initially mainly associated with venous thromboembolism, NETs also affect and mediate atherothrombosis and its acute complications in the coronary, cerebral and peripheral arterial vasculature. In this context, besides deep vein thrombosis and pulmonary embolism, NETs in atherosclerosis and especially its acute complications such as myocardial infarction and ischemic stroke gained a lot of attention in the cardiovascular research field in the last decade. Thus, since the effect of NETosis on platelets and thrombosis in general is extensively discussed in other review articles, this review focusses on the translational and clinical relevance of NETosis research in cardiovascular thrombo-occlusive diseases. Consequently, after a brief summary of the neutrophil physiology and the cellular and molecular mechanisms underlying NETosis are presented, the role of NETosis in atherosclerotic and venous thrombo-occlusive diseases in chronic and acute settings are discussed. Finally, potential prevention and treatment strategies of NET-associated thrombo-occlusive diseases are considered.